Developing a cosmetic formulation containing lipase produced by the fungus Aspergillus terreus - Gabriela Rocha Ramos; Elissa Arantes Ostrosky; Patrícia Santos Lopes; Newton Andréo Filho; Lohanna Luciyanla Kakuda; Jéssica Nascimento da Silva Pinto; Emanuela de Lima Viana; Neyna Santos Morais; Nathalia Saraiva Rios; Ana Paula Barreto Gomes; Francisco Humberto Xavier Júnior; Francisco Caninde de Sousa Junior; et al. (PLoS ONE, 2025)
This study aimed to evaluate the potential of lipase from Aspergillus terreus as an active ingredient in cosmetic formulations. Lipase was produced using the fungus Aspergillus terreus and was immobilized on gel silica as support. The enzymes were characterized using Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Thermogravimetry and Differential Scanning Calorimetry (TG/DSC), and safety evaluation through cytotoxicity tests using NIH-3T3 fibroblast cells. A central composite rotatable design was employed to find the best conditions for enzymatic cosmetic production. The enzyme produced by A. terreus showed activity of 375.9 U/g of substrate, and the immobilized enzyme showed 12.78 U/g of silica, while the lipase from R. oryzae showed activity of 69.91 U/g. As confirmed by FTIR and XRD, SEM showed weak enzyme interaction with silica during immobilization. Cytotoxicity tests showed that only the lipase produced by A. terreus was safe for NIH-3T3 fibroblast cells. The central composite rotatable design showed the agitation time influenced the enzyme activity response. According to the results, the enzyme produced by the fungus A. terreus is a promising and safe product for research into developing new cosmetic products.